Kindle fire HD for dummies - Muir, Nancy C. (John Wiley & Sons, 2013)
Your Kindle Fire HD is loaded with new features, and this book shows you how to take advantage of every one. You can store your Amazon content in the cloud, make Skype video calls, get the fastest Wi-Fi speed, and choose from hundreds of apps, movies, and songs. Follow this guide to start reading, watching, and playing right away!